Pengaruh Personality, Motivasi Intrinsik Lingkungan Kerja Non Fisik Terhadap Organizational Citizenship Behavior Melalui Komitmen Organisasi Sebagai Variabel Mediasi (Studi Kasus di PT. Casuarina Harnessindo Pemalang) - Santi Suciningtyas Suciningtyas; Delaga Nurwisda Nurwisda; Diah Wuriah Ningsih; Arif Hadi Prasetyo (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Facing the current era of globalization, competition between industries is getting tougher, the industry is not only faced with domestic competition, but also abroad. Facing these situations and conditions, the industry needs to ensure its management plans and policies, especially in the field of human resources. Human resource control now represents a propriety and no longer represents an option if the industry wants to develop. This study aims to analyze the influence of Personality, Intrinsic Motivation and Non-Physical Work Environment on Organizational Citizenship Behavior with Organizational Commitment as an Mediation Variable at PT. Casuarina Harnessindo Pemalang. The results of this study indicate that Personality, Intrinsic Motivation and Non-Physical Work Environment on Organizational Citizenship Behavior. Furthermore, it is proven that organizational commitment can mediate the influence of Personality, Intrinsic Motivation and Non-Physical Work Environment on Organizational Citizenship Behavior.